Thrombocytopenia as an important determinant of poor prognosis in patients with pyogenic liver abscess: a retrospective case series - Li, Sheng-zhong; Liu, Shao-hua; Hao, Meng; Yu, Tian; Hu, Song; Liu, Li; Liu, Zhe-long (Frontiers in Surgery, 2023)
Background: Thrombocytopenia and poor prognosis in severe conditions are associated.However, the clinical significance of thrombocytopenia in pyogenic liver abscess (PLA) has not been evaluated.To evaluate the association between thrombocytopenia and the prognosis of patients with PLA.: A consecutive case series of 458 adult patients with PLA hospitalized at Tongji Hospital (Wuhan, China) between October 2011 and June 2021 was included in this cross-sectional analysis. Patient data were compared between the thrombocytopenia and non-thrombocytopenia groups. Multivariate logistic regression, receiver operating characteristic (ROC) curve and propensity score -matched analyses (PSM) were performed. Results: Of the 458 patients with PLA, 94 (20.5%) developed thrombocytopenia, 19 (4.1%) developed septic shock, 14 (3.1%) were admitted to the ICU, and 15 (3.3%) died during hospitalization. Thrombocytopenia was independently associated with shock (95%CI=3.529-57.944, P<0.001), ICU admission (95%CI=1.286-25.733, P=0.022), and mortality (95%CI=1.947-34.223, P=0.004) in multivariate regression analysis. ROC analysis showed that thrombocytopenia may be an identified marker of shock (area under the ROC curve [AUC], 0.8119; cut-off, 92.50; P<0.0001), ICU admission (AUC, 0.7484; cut-off, 82.50; P<0.0015), and mortality (AUC, 0.7827; cut-off, 122.50; P<0.002). These findings remained consistent across 86 pairs of patients analyzed for PSM analyses.Conclusions: Thrombocytopenia is an independent risk factor for poor prognosis in PLA and patients may be more prone to adverse outcomes.